Analysis of the Impact of Perceived Organizational Support and Transformational Leadership on Psychological Well-Being through Job Satisfaction - Rahayu, Tamara Dwi; Subiyanto, Didik; Kirana, Kusuma Chandra (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the impact of the perception of organizational support and transformational leadership on the psychological well-being of employees through job satisfaction. The focus of the research is to understand how these two factors affect the psychological well-being of employees with job satisfaction acting as mediators. This study uses a quantitative approach. The data was collected through a survey with questionnaires distributed to 81 employees of the Yogyakarta Police Human Resources Bureau. The data analysis method used is Structural Equation Modeling (SEM) with the help of SmartPLS 4.0 software. The results of the study show that the perception of organizational support and transformational leadership has a significant effect on job satisfaction and employee psychological well-being. Job satisfaction mediates the influence of perceptions of organizational support and transformational leadership on psychological well-being. This model explains 46.8% of job satisfaction variability and 84.2% of psychological well-being variability. This research confirms the importance of the perception of organizational support and transformational leadership in improving the psychological well-being of employees through job satisfaction. These findings provide actionable insights to improve employee well-being within organizations.